(untitled) (CIPEEX, 2023)
Introduction: The practice of strength training (ST) with physical exercises improves glycemic stability during exercise and reduces the duration and severity of post-exercise hypoglycemia in individuals with type 2 diabetes. Although the effects of strength training (ST) on health are vast in the literature, the acute and subacute response of plasma glucose with circuit strength training (CST) in young individuals is very scarce. Objective: Develop a study protocol on the evaluation of plasma glycemic behavior in healthy young adults before, during, and after circuit strength training with active rest. Methods: This is a cross-sectional study. The participants in this type of study will be selected based on certain variables of interest, informed about the study, and sign the ICF. The participants will be subjected to anamnesis, collection of anthropometric evaluation, in order to outline the physical-functional profile, will be taken to the weight room, where they will remain seated for 10 minutes for pre-protocol capillary blood collection, these will be randomized into 2 groups: one group will undergo a session with a control protocol without exercise and the other, a session with an experimental protocol with circuit strength training. Capillary blood glucose will be collected before, during, and after the protocols. Discussion: From this cross-sectional study protocol, it is expected to contribute additional information on the understanding of the acute and subacute effects of plasma glycemia with circuit strength training, with active rest, in young individuals, thus providing a safer TFC prescription.